The Study of Technical and Scientific Translation: An Examination of its Historical Development - Javier Franco Aixelá (JoSTrans: The Journal of Specialised Translation)
This article tries to show and explain in some detail the quantitative and qualitative evolution of the bibliography on technical and scientific translation throughout history as compared with other research fields. The underlying corpus drawn on are the more than 20,000 entries collected in BITRA (Bibliography of Interpreting and Translation) up to September 2003. This bibliographical tool is an online multilingual database which attempts to comprise everything ever published on translation and can be freely accessed on http://www.ua.es/dfing/tra_int/bitra_en.htm The paper concludes that concern for technical and scientific translation only appears in the 1950s, when obsession with canonicity seems to decline somewhat within Translation Studies. A further finding is that consideration of this type of translation has been and remains mainly practical, with reflections on problems posed by terminological domains (mostly legal and, lagging far behind, medical, business and IT), teaching, documentation, the interpreting of technical discourse and professional issues as the favourite topics.